Depthwise evaluation of total dissolved solids and arsenic from a drilled borehole near River Ravi, Lahore, Pakistan - Habib Ur Rehman; Mujeeb Ur Rahman; Saeed Ahmed (Journal of Water and Climate Change, 2023)
Groundwater pollution is now a significant threat to the ecosystem. The untreated disposal of municipal and industrial wastes through drains into water bodies (rivers, lakes, and canals) is the primary source of contamination. The highly contaminated water harms individual health. In this study, total dissolved solids (TDS) and arsenic (As) mobilization were explored depthwise from a drilled borehole at main Raiwind Road, Thokar Niaz Baig, near River Ravi, Lahore. The concentrations of TDS and As in the aquifer indicate that the top shallow aquifer bearing high salts occurred due to local inputs of waste effluents discharged into the River Ravi. In contrast, at deep shallow aquifers, enrichment of As with elevated pH results from the geochemical oxidative dissolution process. The results showed that natural and anthropogenic activities influence groundwater throughout the depth. The TDS and As concentrations were found above the World Health Organisation (WHO) guideline values at some depth intervals, which are harmful to human health. HIGHLIGHTS Depthwise evaluation of total dissolved solids and arsenic from drilled borehole is performed.; Concentration of TDS and arsenic varied from shallow to deep groundwater.; Groundwater quality is changing due to natural and anthropogenic activities.;